2003
DOI: 10.1086/379639
|View full text |Cite
|
Sign up to set email alerts
|

Cold Dust in Kepler's Supernova Remnant

Abstract: The timescales to replenish dust from the cool, dense winds of Asymptotic Giant Branch stars are believed to be greater than the timescales for dust destruction. In high redshift galaxies, this problem is further compounded as the stars take longer than the age of the Universe to evolve into the dust production stages. To explain these discrepancies, dust formation in supernovae (SNe) is required to be an important process but until very recently dust in supernova remnants has only been detected in very small … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 32 publications
(44 reference statements)
5
55
0
Order By: Relevance
“…In fact, while submillimetre observations of the Kepler and CasA SN remnants yield 0.1-1 M of dust (e.g. Morgan et al 2003;Dunne et al 2009;Gomez et al 2009), infrared observations give 0.1 M of dust (Helmhamdi et al 2003;Sugerman et al 2006;Kotak et al 2009;Rho et al 2008Rho et al , 2009Meikle et al 2007;Takaya et al 2008). A possibility is that such a discrepancy could be traced back to a difference in the instrument sensitivity to the different dust phases (cold for submillimetre, warm for Spitzer).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, while submillimetre observations of the Kepler and CasA SN remnants yield 0.1-1 M of dust (e.g. Morgan et al 2003;Dunne et al 2009;Gomez et al 2009), infrared observations give 0.1 M of dust (Helmhamdi et al 2003;Sugerman et al 2006;Kotak et al 2009;Rho et al 2008Rho et al , 2009Meikle et al 2007;Takaya et al 2008). A possibility is that such a discrepancy could be traced back to a difference in the instrument sensitivity to the different dust phases (cold for submillimetre, warm for Spitzer).…”
Section: Introductionmentioning
confidence: 99%
“…The formation and evolution of dust in primordial SNe as well as the dust evolution effects on SED of galaxies have been studied by Nozawa et al (2008) and Schurer et al (2009), respectively. Studies of the gas, metal and dust evolution have been performed by means of analytical models (Elvis et al 2002) and simulations (Dwek 1998;Morgan et al 2003;Inoue 2003;Valiante et al 2009a), Calura et al (2008) applied a detailed formulation of dust production and destruction to a detailed chemical evolution model. In that paper the model was mostly constrained by means of the solar neighbourhood dust determination, and then it was proven to be quite flexible, since it can be readily applied to models for elliptical and irregular galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…3) located at a distance of 11,000 light years from Earth. When we turned our infrared (Spitzer) and submillimetre (SCUBA) eyes onto Cas A to look for warm dust (Rho et al 2008) and cold dust respectively (Dunne et al , 2009Morgan et al 2003), we found evidence that exploding stars like Cas A could be responsible for littering our universe with dust grains. However, there could be other mechanisms responsible and we need to observe supernovae from space to test this theory.…”
Section: The Smoking Supernova Educational Projectmentioning
confidence: 99%
“…Sugerman et al 2006;Meikle et al 2007;Blair et al 2007;Rho et al 2008;Wesson et al 2010a), corresponding to condensation efficiencies which are at least two orders of magnitude smaller than theoretical models predict (Todini & Ferrara 2001;Bianchi & Schneider 2007). FIR and sub-mm observations of dust within supernova remnants (SNR) estimate masses ranging from 0.1−1 M Morgan et al 2003;Gomez et al 2009), yet there are a number of difficulties with the interpretation of these results. It is obvious that there is now indeed clear observational evidence for dust formation in CCSNe, but the quantity of dust formed within the ejecta is still a subject of debate.…”
Section: Introductionmentioning
confidence: 99%